(Fake) News is Racist: Mapping Culturally Relevant Approaches to Critical News Literacy Pedagogy - Higdon, Nolan; Butler, Allison (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2023)
Fake news, while problematic in its own way, is not an anomaly and though intimately connected to the Trump administration, did not begin, nor end, with his administration. Fake news is part of a larger environment of racism in the structure of the news, where stories of People of Color are often skewed in a negative way, positive contributions from People of Color are ignored, and where journalists of color may be sidelined. However, there is a dearth of news literacy curricula that centralizes the stories of People of Color. This is particularly problematic given the ways in which news perpetuates racism. This study utilizes critical media literacy coupled with critical race theory to develop culturally responsive news literacy curricula that centralizes stories about bodies of color as a way to make more comprehensive sense of our news and information media.